An efficient method for the correction of iatrogenic symmastia: A case series. (May 2018) - Zingaretti, Nicola; De Biasio, Fabrizio; De Lorenzi, Francesca; Massarut, Samuele; Parodi, Pier Camillo
Abstract: Background: Symmastia is a medial confluence of the breasts, produced by a web of skin and fat merged across the midline, that generates the disappearance of the intermammary sulcus. Apart from the rare congenital cases, this condition is usually a result of technical complications during breast augmentation surgery. This article describes a simple and reliable method for correcting symmastia. Methods: From November 2006 to June 2015, we treated 10 patients with acquired symmastia who had previously undergone an implant-based reconstruction. We performed a crescent-shape medial capsulectomy and we then performed an adequate and resistant closure with a substitute device, consisting of a Tuohy epidural needle and polydioxanone sutures, which are easily accessible and inexpensive. The process outcome was successful and resulted in a normal cleavage between the breasts. Results: Mean follow-up was 24 months. We haven't observed any recurrence of symmastia to date in this study. One postoperative hematoma and one seroma occurred. All ten patients achieved acceptable results through the procedure. Conclusion: Our pericapsular Tuohy technique for medial closure of the pocket is a practical and efficient substitute to traditional capsulorraphy and provides reliable and reproducible results. Highlights: An easy way for perform a medial capsulorraphy. It provides reliable and reproducible results. Useful when it's not possible to perform classical capsulorraphy.